2009
DOI: 10.1136/bmj.b4460
|View full text |Cite
|
Sign up to set email alerts
|

Slow walking speed and cardiovascular death in well functioning older adults: prospective cohort study

Abstract: Objective To study the relation between low walking speed and the risk of death in older people, both overall and with regard to the main causes of death. Design Prospective cohort study. Setting Dijon centre (France) of the Three-City study. Participants 3208 men and women aged ≥65 living in the community, recruited from 1999 to 2001, and followed for an average of 5.1 years. Main outcome measures Mortality, overall and according to the main causes of death, by thirds of baseline walking speed (measured at ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
212
5
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(235 citation statements)
references
References 32 publications
10
212
5
8
Order By: Relevance
“…5) As shown in the histograms of the Figure, our results indicate that 6.4% of men and 23.8% of women in the middle-aged AMI subgroup, and 28.8% of men and 43.5% of women in the elderly AMI subgroup, had a walking speed slower than those reported in the previous cohort study; this was not the case in the non-AMI group. The recommended walking speed for crossing over the road at a signalized intersection is reported to be 1.0-1.2 m/second (60-70 m/minute) for community-dwelling people.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…5) As shown in the histograms of the Figure, our results indicate that 6.4% of men and 23.8% of women in the middle-aged AMI subgroup, and 28.8% of men and 43.5% of women in the elderly AMI subgroup, had a walking speed slower than those reported in the previous cohort study; this was not the case in the non-AMI group. The recommended walking speed for crossing over the road at a signalized intersection is reported to be 1.0-1.2 m/second (60-70 m/minute) for community-dwelling people.…”
Section: Discussioncontrasting
confidence: 45%
“…[1][2][3][4][5] A recent prospective cohort study reported that a slower walking speed was strongly associated with cardiovascular mortality in a population of well-functioning elderly people. 5) The Heart Failure and A Controlled Trial Investigating Outcomes of Exercise TraiNing (HF-ACTION) showed that greater clinical benefits, such as reduced mortality or hospitalization, were observed among patients with heart failure who adhered to a higher volume of exercise, which was calculated by multiplying exercise intensity by the time spent exercising. 6,7) Patients with chronic heart failure in this trial participated in supervised exercise training, followed by a 3-month home-based exercise program.…”
mentioning
confidence: 99%
“…Diversos estudios epidemiológicos sobre los factores contribuyentes y asociados a una velocidad de la marcha lenta muestran información que varía según el escenario y la población estudiada (6)(7)(8) . Estos hallazgos sugieren la existencia de determinantes ajenos a la propia edad que de estar presentes puedan contribuir a detectar precozmente una velocidad de la marcha lenta en adultos mayores aparentemente sanos; por ello es necesario identificar aquellos factores que, al no depender de la edad, sean modificables y permitan intervenir en mejorar la velocidad de la marcha.…”
Section: Mensajes Claveunclassified
“…Likewise, slow walking speed in older people has been shown to be strongly associated with an increased risk of cardiovascular mortality [8]. An algorithm developed by the European Working Group on Sarcopenia in Older People (EWGSOP) [9] to identify sarcopenia proposed gait-speed measurement as the first step of the algorithm.…”
Section: Introductionmentioning
confidence: 99%